Answer:
I(x) = P(4x)
Step-by-step explanation:
We have the point (2, -4) for P(x) and the point (1/2, -4) for I(x)
So, we can see that
I(x) -----------> P(x)
(1/2, -4) -----> ( 4(1/2), -4) = (2, -4)
Therefore, I(x) = P(4x)
Because the coordinate of x in I(x) has to be multiplied by 4 to get the same coordinate of y in P(x).
For example, P(x) passes through the point (x, P(x)) = (4, 8). Then I(1) = P(4(1)) = P(4) = 8. So, I(x) passes through the point (1, 8)
Then, the correct transformation of P(x) to get I(x) is
I(x) = P(4x)